Pemanfaatan Akun Instagram @kulinerdilombok dalam Memasarkan Wisata Kuliner di Lombok - Vivia Pauline Harliana; Monika Teguh (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This research analyzed how the Instagram account @kulinerdilombok is managed to market culinary businesses in Lombok. After the 2018 Lombok earthquake and the COVID-19 pandemic, the use of social media as a marketing medium is crucial to revive culinary businesses in Lombok. Social media has become an important tool for culinary entrepreneurs. This study aims to determine the activities carried out by the Instagram account @kulinerdilombok in promoting culinary tourism in Lombok. Effective messaging through social media is needed to reach a wider audience. Using interview and documentation methods, this study identified how communication elements are implemented in the use of Instagram as a marketing medium. The findings reveal that over the past six years, @kulinerdilombok has grown its audience to 62,000 followers by managing the account with a focus on context, communication, collaboration, and connection. The account has significantly impacted both business owners and the public seeking information about Lombok’s culinary scene. This study offers a reference framework for individuals and organizations aiming to build and strengthen public engagement in the digital era through effective communication on Instagram.